2021
DOI: 10.1128/mbio.00047-21
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudomonas aeruginosa Antimicrobial Affects the Biogeography but Not Fitness of Staphylococcus aureus during Coculture

Abstract: Pseudomonas aeruginosa and Staphylococcus aureus are two of the most common coinfecting bacteria in human infections, including the cystic fibrosis (CF) lung. There is emerging evidence that coinfection with these microbes enhances disease severity and antimicrobial tolerance through direct interactions. However, one of the challenges to studying microbial interactions relevant to human infection is the lack of experimental models with the versatility to investigate complex interaction dynamics while maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 64 publications
3
43
0
Order By: Relevance
“…4C). This indicates that, in absence of HCN, S. aureus growth is stimulated by P. aeruginosa, which further emphasizes that these two bacteria could engage in complex negative and positive interactions in vivo (67,68).…”
Section: S Aureus Had Been Regarded As One Of the Initial Microbial C...mentioning
confidence: 87%
“…4C). This indicates that, in absence of HCN, S. aureus growth is stimulated by P. aeruginosa, which further emphasizes that these two bacteria could engage in complex negative and positive interactions in vivo (67,68).…”
Section: S Aureus Had Been Regarded As One Of the Initial Microbial C...mentioning
confidence: 87%
“…To uncover the reason for the worsening clinical manifestation, the processes allowing these two microbes to survive together need to be better understood. Various studies have shown that different stages of growth and environmental conditions, including media and planktonic versus biofilm modes of growth, can promote the coexistence of S. aureus and P. aeruginosa ( 9 , 12 , 13 ). In some other cases, it has been found that bacterial segregation promotes survival ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that different stages of growth and environmental conditions, including media and planktonic versus biofilm modes of growth, can promote the coexistence of S. aureus and P. aeruginosa ( 9 , 12 , 13 ). In some other cases, it has been found that bacterial segregation promotes survival ( 13 ). On the other hand, many in vitro studies have shown that P. aeruginosa itself or P. aeruginosa factors, such as secreted LasA and rhamnolipids, can lyse or kill S. aureus ( 7 , 14 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously recognized that spatial organization facilitated by an undisturbed growth environment can facilitate the co-existence of bacteria, including P. aeruginosa and S. aureus (52).…”
Section: Discussionmentioning
confidence: 99%